Using Nanomaterials in Stabilization of Soil for Oil Infrastructures - Majeed, Dr. Zaid Hameed; Aubais, Eng. Kadhim Jawad; Taha, Dr. Mohd Raihan (Journal of Petroleum Research and Studies, 2020)
The design foundations of storage tanks for oil industry experiences significant problems due to the widespread occurrence of weak and compressible soil which resulted in foundation failure. In this study, soft soils were taken from two locations and mixed with three types of nanoparticles which were nano-alumina (nano Al2O3), nano-copper (nano CuO), and nano-magnesium (nano MgO). Nanomaterials were incorporated in small percentage (less than 1%) by dry weight of soil. The tested geotechnical characteristics included the water content, dry density, and the unconfined compressive strength. The results showed significant enhancements in the maximum dry density and unconfined compressive strength. The level of enhancement depended on the type of nanomaterials and the contents. Improved strength and hardening properties were shown with the utilization of nano CuO material in comparison to the soil samples with the other nanomaterials additions, with its optimum addition of 0.7% provided an increment rate of 662.7% while the optimum nano CuO which is about 1% showed a 532% increasing rate in the compressive strength of S1 soil. It was noted that the maximum dry density and unconfined compressive strength enhanced with the increase in the nanoparticles content until reaching a percentage in which the strength decreased. The optimum content of the nano MgO was 0.3% while the optimum nano Al2O3 content was about 0.3% for soil S1 and was about 0.1% for soil S2. The presence of nanomaterials in excessive contents caused agglomeration of particles which had negative influences on mechanical characteristics of the soils. Generally, the incorporation of finer particles like nanoparticles even with low amount would improve the geotechnical characteristics of soils with the consideration of the potential environmental benefits, these combined admixtures are intended to lower the cost and become a more sustainable and environmental alternative for soil stabilization